MENDUKUNG INDUSTRI PERTAHANAN DENGAN ANALISA PROSES PENGOLAHAN BESI SPONS DARI PASIR BESI SEBAGAI BAHAN BAKU BAJA - Zaman, Qomaru; Johan, Firman; Nugroho, Hervianto (AGUSPATI Research Institute, 2022)
In coastal areas, there are generally a lot of sand deposits that contain iron sand and many particles contained in it. This iron sand is generally shaped like a rock with high mineral content and because of the weather this rock is eroded by water and sea waves so that it feels like it is being washed. In this condition, iron sand is generally black or gray and tends to be dark. The mineral content in iron sands is usually opaque minerals mixed with granular minerals, calcite, amphbole, quartz, feldspar, biotite, pyroxene, and tourmaline. In addition to this composition, iron sand contains titaniferous magnetite, magnetite, hematite, hematite, basaltic and volcanic andesitic. The methods used in thiss research is to observed and experiment the process of making sponge iron. The method and concept is similar to a cake-making experiment by mixing several raw materials to produce the best composition. In addition to getting the best composition, the process during mixing will also be observed and combined with the results of the composition of the raw materials. From the results of laboratory tests, the composition with variations A2, namely the addition of silica sand by 20% can produce the greatest chemical content of Fe. that is equal to 60.44%. While the lowest chemical content was obtained in the A3 variation with the addition of 20% activated carbon composition. In this condition, research with the addition of silica sand can be increased so that the obtained Fe content can increase.